Rancang Bangun Pendataan Stok Barang Operasional Dengan Metode Iconix Process Di HRP Foto Copy Berbasis Web - Wahyu Agung Pratama; Zulham Sitorus (Bulletin of Information Technology (BIT), 2023)
HRP Fotocopy is a business engaged in the sale of stationery and printing goods. However, along with the development of business and the world of technology, the sales and purchasing processes are increasing, while the processes carried out by the HRP are still carried out manually, resulting in a buildup of files and longer services. The development of the times is followed by the role of computer technology which is increasingly rapidly making business competition more stringent, thus HRP Foto Copy builds a stock information system application using the Software Development Life Cycle (SDLC) concept. One of the SDLC frameworks is Use Case Driven Object Modeling with UML or what is commonly called the ICONIX process. Utilization of information technology with the Iconix Process method greatly assists business parties in developing systems according to needs with the Iconix Process concept which completes the stages up to the evaluation stage